Acute Cardiovascular Adaptation to Strenuous Exercise: An Integrative Ultrasound Study. (29th July 2018) - Bianchini, Elisabetta; Bruno, Rosa Maria; Di Lascio, Nicole; Vezzoli, Alessandra; Mrakic‐Sposta, Simona; Corciu, Anca Irina; Comassi, Mario; Pratali, Lorenza
Abstract : Objectives: The aim of this study was to evaluate the acute effects of participation in an Ironman distance triathlon competition on arterial function by ultrasound, in relation to cardiac function and body water content. Methods: Twenty‐eight male triathletes participating in an Ironman distance competition underwent carotid, femoral, and cardiac ultrasound examinations. Moreover, the presence of extravascular lung water was identified by lung echo B‐lines (echogenic coherent wedge‐shaped signal with a narrow origin from the hyperechoic pleural line) at rest and within 20 minutes of arrival. Results: At the end of the competition, athletes showed an increased heart rate (mean ± SD, from 60.2 ± 13.1 to 82.8 ± 15.6 beats/min; P < .0001) and unchanged mean blood pressure (from 93 ± 14 to 91 ± 10 mm Hg; P > .05) in the presence of negligible dehydration (total body water from 48.0 ± 4.0 to 46.5 ± 3.9 kg; P > .05). Cardiac output increased (from 5.5 ± 1.2 to 6.7 ± 2.4 L/min; P < .05) in the presence of an unchanged stroke volume (from 64 ± 14 to 59 ± 16 mL; P > .05) and unchanged left ventricular elastance (from 1.52 ± 0.48 to 1.39 ± 0.48 mm Hg/mL/m 2 ; P > .05). The mean carotid diameter increased (from 7.19 ± 0.65 to 7.61 ± 0.76 mm; P < .05), whereas the mean femoral diameter was unchanged at the end of the competition (from 10.41 ± 0.83 to 10.49 ± 0.82 mm; P > .05). Carotid intima‐media thickness was significantly reduced (from 537 ± 70 to 495 ± 70 μm; P < .05), whereas B‐lines increased significantly after the competition (from 1 [0–4] to 12 [5–23]; P < .0001). Conclusions: These data suggest different acute functional adaptation in central arteries with respect to peripheral leg vessels.